Investigation of juices with pulp obtained from stone fruit - Lugovska, Oksana (My University, 2017)
This article is that juices occupy the leading place in the human diet. Along with the increase in the volume of juice production and the expansion of their range, the technology of their production is improved, with the purpose of preserving the biologically active substances of raw materials, improving the quality and nutritional value of the finished product. Current and necessary introduction of standards for methods of determining the indicators that allow establishing the naturalness of juices provide a regulatory framework for eliminating the sale of counterfeit products to consumers and create priority conditions for responsible manufacturers. This work is devoted to the examination of the chemical composition and nutritional value of juices with pulp obtained from stone fruits, to the conformity with the standard DSTU 4150: 2003 Juices, juice drinks, fruit nectars, vegetables and melons. General technical conditions. Ця стаття полягає в тому, що соки займають провідне місце в харчуванні людини. Поряд з збільшенням обсягу виробництва соку та розширенням їх асортименту, технологія їх виробництва поліпшується з метою збереження біологічно активних речовин сировини, підвищення якості та харчової вартості готового продукту. Поточне та необхідне запровадження стандартів для методів визначення показників, що дозволяють встановити природність соків, забезпечує регуляторну базу для усунення продажу споживачів контрафактної продукції та створення пріоритетних умов відповідальних виробників. Дана робота присвячена дослідженню хімічного складу та харчової цінності соків з м'якоттю, отриманої з кам'яних фруктів, до відповідності стандарту ДСТУ 4150: 2003 Соки, сокові напої, фруктові нектари, овочі та баштан. Загальні технічні умови.
Keywords: кафедра експертизи харчових продуктів; falsification; apricot; peach juice; minerals; vitamins; фальсифікація; абрикос; персиковий сік; мінерали; вітаміни